Flexible piezoresistive strain sensor based on optimized elastomer-electronic polymer blend. (15th January 2021) - Panwar, Varij; Anoop, Gopinathan
Graphical abstract: Highly ductile P(VDF-TrFE-CTFE)/PEDOT:PSS blend shows high dielectric constant and high gauge factor bending cycle. Highlights: Elastomer-Electronic Polymer blend shows high gauge factor with high dielectric constant. Elastomer-Electronic Polymer blend shows high ductility. Elastomer-Electronic Polymer blend shows stable sensing signals with bending cycles of 6500. Abstract: Biocompatible polymer-based sensors have unique advantages over semiconductor-carbon-based, and metal-based piezoresistive sensors because of the flexible nature, high gauge factor, and high bendability of the polymers. In this study, various compositions of biocompatible Poly(vinylidene fluoride-trifluoroethylene- chlorotrifluoroethylene) P(VDF-TrFE-CTFE) (TER)/poly(3, 4-ethylene dioxythiophene) (PEDOT):poly(styrene sulfonate) (PSS) elastomer-electronic polymer blends were developed using cost-effective blending method for piezoresistive strain sensor. The TER /PEDOT:PSS polymer blend with an optimized blending ratio of 40/60 produced a gauge factor of around 680 with a high dielectric constant and a high mechanical strain of 221%. The TER/PEDOT:PSS polymer blend shows stable and repeatable response sensing signals up to 6500 bending cycles at a bending strain of 0.009 and checked for the duration of sixty days. The SEM analysis shows the penetration of the PEDOT:PSS particles between the backbone of TER polymer in the optimized TER/PEDOT:PSS polymer blend, which enhances the gauge factor of the TER/PEDOT:PSS blend sensors. Owing to high ductility and high sensitivity, our proposed elastomer-electronic polymer blend with ~0.18 mm thickness will find applications in wearable and electronic skin technology.